Estratégias midiáticas de uma popstar na internet : Avril Lavigne no Orkut - Matta, João Osvaldo Schiavon (2008)
Media culture has been dominant in the daily life of various types of public, including young people. The cult of celebrities is a social practice that is present in the internet and it is interwoven in a media system that is occupied by different types of logic, including that of the cultural industry. Nowadays, an industrial culture of entertainment uses media as an ally in order to achieve its business targets. At the same time, young people appropriate spaces of this same media culture in order to establish group cults to superstars. As part of the media system, the internet has been a privileged locus to focus on symbolic constructions and social appropriations by young audiences. In this area, it is possible to make up different types of identities. There are several ways to build the self within cyberspace. Among the identity constructions which are made possible by the content produced in the internet, we can emphasize the veneration and rejection of ephemeral musical idols. Taken as media products, these idols can function as identity matrixes for young people who take part in communities in cyberspace. In view of all this, the present dissertation studies the media strategies that produce celebrities in the internet. We intend to study the admiration processes of pop singer Avril Lavigne´s fans and antifans. She is a star from the musical universe that intensily affects young people around the world, including Brazillian youths. Our objectives are to study the media production concerning Avril Lavigne in the internet as well as the several types of mediation present in this territory.